Construction and expression of Mycobacterium tuberculosis fusion protein AR2 and its immunogenicity in combination with various adjuvants to form vaccine. (December 2022) - Wang, Xiaochun; Du, Jianpeng; Zhang, Yanpeng; Zhu, Tao; Mao, Lirong; Xu, Lifa; Shi, Zilun; Zhang, Jingyan; Sun, Qishan; Qi, Zhiyang; Xia, Lu
Abstract: Tuberculosis (TB) is recognized as a highly infectious disease worldwide, and Bacille Calmette–Guerin (BCG) remains the only TB vaccine licensed for clinical use. As there is little evidence that BCG is effective in adults, there is an urgent need for a safe and effective vaccine to control TB in adults. In this study, we tested the immunomodulatory efficiency of the fusion protein AR2. whole blood IFN-γ release assay (WBIA) was used to detect antigen specificity. The immunogenicity of the vaccine was tested in C57BL/6 mice, and confirmed by enzyme-linked immunosorbent assay (ELISA), flow cytometry, and qRT-PCR. The fusion protein AR2 was successfully constructed and expressed. The level of IFN-γ in the peripheral blood of subjects stimulated by AR2 was significantly higher than in those induced by all subcomponent proteins. AR2-specific IgG and the Th1 cytokines IFN-γ, TNF-α, and iNOS were significantly increased in the group treated with the fusion protein and compound adjuvant (AR2+DMC). Likewise, the number of IFN-γ + CD4 +, IFN-γ + CD8 +, and IL-4 + CD8 + T lymphocytes increased significantly. The combination of the fusion protein and the compound adjuvant (AR2+DMC) may be a suitable candidate for an enhanced TB vaccine. This study provides theoretical and experimental support for future research to enhance the effectiveness of TB vaccines and provides an experimental basis for evaluating the influence of different adjuvants on vaccine efficacy.